2017
DOI: 10.1103/physrevd.96.026017
|View full text |Cite
|
Sign up to set email alerts
|

Mock modular index of M2-M5 brane systems

Abstract: Publisher's copyright statement:Reprinted with permission from the American Physical Society: Physical Review D 96, 026017 c (2017) by the American Physical Society. Readers may view, browse, and/or download material for temporary copying purposes only, provided these uses are for noncommercial personal purposes. Except as provided by law, this material may not be further reproduced, distributed, transmitted, modied, adapted, performed, displayed, published, or sold in whole or part, without prior written perm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…In this brane setup the large N limit of the Chern-Simons matrix model corresponds to an infinite number of intersecting M2-branes, which would lead to an M5-brane as a condensate of M2-branes. In [58,59] we found that a certain configuration of intersecting M2-M5 branes on a two-dimensional plane can be effectively described by the supergroup WZW model associated to the affine Lie superalgebra. Since we have found a connection to the affine Lie superalgebra in this work, we believe that further physical explanation and application can be available in string and M-theory.…”
Section: Discussionmentioning
confidence: 99%
“…In this brane setup the large N limit of the Chern-Simons matrix model corresponds to an infinite number of intersecting M2-branes, which would lead to an M5-brane as a condensate of M2-branes. In [58,59] we found that a certain configuration of intersecting M2-M5 branes on a two-dimensional plane can be effectively described by the supergroup WZW model associated to the affine Lie superalgebra. Since we have found a connection to the affine Lie superalgebra in this work, we believe that further physical explanation and application can be available in string and M-theory.…”
Section: Discussionmentioning
confidence: 99%
“…• Boundary conditions for N ≥ 4 Chern-Simons matter theories: It would be intriguing to understand N = (0, 4) boundary conditions for 3d N ≥ 4 Chern-Simons matter theories [50,51,52]. The analysis of N = (0, 2) boundary conditions for 3d N = 2 Yang Mills-Chern-Simons theories in [30], which argues the level-rank duality of boundary conditions, may be generalized by including two-dimensional chiral superalgebras [28,53], as the construction of these theories is intimately related to the supergroup structure.…”
Section: Future Workmentioning
confidence: 99%
“…In particular a configuration of an NS5-brane with N D3-branes ending on its left and M D3-branes ending on its right can be associated with the dominant integrable weight λ of u(N|M). The same discussion has been done in the context of a configuration consisting of an M5-brane with an M2brane on only one side [29,30]. In this work some particular indices were calculated for this system and its relation to the highest weight atypical module was elucidated using the Kac-Wakimoto formula.…”
Section: Remark 2: Some Comments On the Algebra Of Holomorphic Curves...mentioning
confidence: 96%
“…We begin this section by reviewing the supergroup WZW models. The supergroup WZW model [29,30] is described by the maps f : Σ → (supergroup)SG from a two dimensional Euclidean Riemann surface Σ to the supergroup SG and its dynamics is given by the action…”
Section: Remark 2: Some Comments On the Algebra Of Holomorphic Curves...mentioning
confidence: 99%